Rodinný dům s kancelářemi v Prievidzi - Szakács Bahnová, Eliška (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Bakalářská práce se zabývá návrhem a projektovou dokumentaci rodinného domu s kancelářemi v Prievidzi. Objekt je částečně podsklepen a má tři nadzemní podlaží. Dům je určen k bydlení 2 rodin, nachází se zde 2 bytové jednotky. Prostory kanceláří se nachází v 1. nadzemním podlaží a umožňuje bezbarierové užívaní.Střecha domu je jednoplášťová plochá střecha.

This bachelor´s thesis deals with a design and a project documentation of detached house with office in Prievidza. The object is partial besamet and it has got three above- ground floors. The house is designed for two family. There are two dwelling units. Office is placed in the first floor and it allows access for disabled person. The roof of the house is single flat roof.
Detached house with offices in Prievidza
Keywords: Rodinný dům; kancelář; nadzemní podlaží; částečně podsklepený; plochá střecha; provoz; bytová jednotka; garáž; terasa; Detached house; office; above-ground floor; partial besement; flat roof; business; residentail unit; garage; terrace